2014
DOI: 10.3109/01443615.2014.935717
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of breast cancer in Taiwan, 1971–2010: Temporal changes and an age–period–cohort analysis

Abstract: The current paper describes the age, period and cohort effects on breast cancer mortality in Taiwan. Female breast cancer mortality data were collected from the Taiwan death registries for 1971–2010. The annual percentage changes, age- standardised mortality rates (ASMR) and age–period–cohort model were calculated. The mortality rates increased with advancing age groups when fixing the period. The percentage change in the breast cancer mortality rate increased from 54.79% at aged 20–44 years, to 149.78% in tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
(25 reference statements)
3
16
0
Order By: Relevance
“…Our age-dependent incidence and mortality curves, both showing increase with age, were similar to 10-years older SEER data [ 4 ] and 20-years older U.S. data [ 15 ]. Our age-dependent mortality trends were somewhat also similar to Taiwanese data [ 22 ]. Age-dependent mortality and incidence of our study were different from trends observed for Asia-Oceania [ 15 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our age-dependent incidence and mortality curves, both showing increase with age, were similar to 10-years older SEER data [ 4 ] and 20-years older U.S. data [ 15 ]. Our age-dependent mortality trends were somewhat also similar to Taiwanese data [ 22 ]. Age-dependent mortality and incidence of our study were different from trends observed for Asia-Oceania [ 15 ].…”
Section: Discussionsupporting
confidence: 87%
“…APC analysis overcomes this by introducing a priori constraints, with concomitant report of absolute measures [ 11 , 13 , 20 , 21 ]. Description of population based breast cancer programs are fraught with data interpretation challenges [ 5 , 6 , 11 , 13 , 22 ], where accounting for age, period and cohort augment descriptive data analysis [ 20 , 21 ]. Thus, our objective was to provide a multi-scalar description of incidence and mortality due to breast cancer in women from Germany for the longitudinal period 1999–2008.…”
Section: Introductionmentioning
confidence: 99%
“…The trend in Asia contrasts to most western countries, where the mortality rates of breast cancer remained unchanged or were even declining over the last decade . In Taiwan, for example, breast cancer patients with an age range of 45‐64 years have a 2‐fold increase in the number of death cases from 1919 (per 100 000 inhabitants) in 1991‐1995 to 4484 (per 100 000 inhabitants) in 2006‐2010 . Even without insights into the risk factors that contribute to the treatment failure in Asian patients with breast cancer, we speculate that the Asian population is excessively exposed to environmental chemicals in their daily life.…”
Section: Introductionmentioning
confidence: 88%
“…1 According to the statistics of the Ministry of Health and Welfare, since 1995, breast cancer has been the most common femalespecific malignancy in Taiwan. 2 Identified risk factors for breast cancer includes old age, geographic location, a family history of breast cancer, genetic mutations, exposure to ionizing radiations, a history of a benign breast disease, high mammographic density, early menarche and late menopause, nulliparity or old age at first childbirth, exogenous hormone use, lifestyle (alcohol, diet, obesity, and physical activity), and high prolactin levels. 3,4 All the aforementioned risk factors have been associated with breast cancer; however, the operative mechanisms underlying the disease remain unclear and must be further investigated to effectively improve the prevention, treatment, and prognosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%